Delavska participacija v evropski delniški družbi v Evropski uniji in Sloveniji - Kodrič, Tjaša (Podjetje in delo, 2022)
This article discusses Council Regulation (EC) No 2157/2001 of 8 October 2001 on the Statute for a European company (SE) and Council Directive 2001/86/EC of 8 October 2001 supplementing the Statute for a European company with regard to the involvement of employees. The aforementioned regulation or SE Regulation represents a turning point in the field of European economic law, as it finally introduced a new form of company after lengthy negotiations, i.e. Societas Europaea or SE. The regulation is thus part of the so-called Societas Europaea (SE) Statute, finally adopted on 8 October 2001. The SE Statute consists of the above-mentioned SE Regulation and the Council Directive 2001/86/EC of 8 October 2001 supplementing the Statute for a European company with regard to the involvement of employees. Employees' participation was the biggest problem in the adoption of the previously mentioned SE Statute and for the purpose of resolving this issue, the Employees' Participation Directive has been adopted. The main goal of the article is to study and analyse the participation of employees in SE management. When setting it up, the choice of the method of management, i.e. one- or two-track system is left to the founders of the SE. The two-tier management system is closely related and more favourable for the participation of employees in the management of companies. Following the implementation of the SE Regulation, the new Companies Act (ZGD-1) thus enabled Slovenian companies to choose between a one- and two-tier management system. In order to understand certain concepts in the following chapters, we first focus on SE in general before discussing the main issue. Then we present the background, i.e. the turbulent history of the SE formation and the purposes and objectives of the SE Statute. The main purpose of the SE Regulation was, in general, to establish a new form of company to facilitate the operation of economic operators in several Member States of the European Union. The Employees' Participation Directive thus complements the SE Regulation and ensures that the creation of the SE does not lead to the disappearance or reduction of employee integration practices that exist in companies participating in the founding of the SE. Finally, we focus on the implementation of the SE Statute into Slovenian legislation and its impact on the creation of new legislation, with specific analysis of Participation of Workers in Management of the European Public Limited-Liability Company Act (SE).